The Pre-Raphaelite city and the trap of modernity - Raphaël Rigal (Angles)
The poetic and pictorial works of the “Pre-Raphaelite galaxy”, as one might call the group formed by Dante Gabriel Rossetti, the Pre-Raphaelite Brotherhood, and their artistic kindred, exhibit an ambiguous relationship to Victorian modernity and 19th-century technical and political “progress”, especially British urbanisation. As urban-living people, the Pre-Raphaelites were always in direct contact with the modern city and its evolutions, and if the urban context is not their one major topic, the paintings and poems that come to grasp with it from the late 1840s onward are the strongest proponents of what could be called an alter-modern philosophy: the acceptance of some aspects of modern society, combined with the rejection of its dehumanizing and alienating excesses, to form a via media, an alternative to untamed Progress and unchecked urbanisation. The return to Nature they advocate is not just a nostalgic look backwards, but a real way of life based on simplicity, common decency, and the equality of all mankind – a vision which comes to life in the 1880s in William Morris’s socialist pamphlets and proposals for a new city. We shall base our demonstration on a set of four poems: Christina Rossetti’s “The Dead City” (1840) and “Goblin Market” (1862), Dante Gabriel Rossetti’s “Jenny” (1848-1869), and William Bell Scott’s “Maryanne” (1854), and compare them with D. G. Rossetti’s painting The Gate of Memory (1857-1864) and some of William Morris’s essays. This corpus constitutes an ensemble of works answering one another, and openly attacking the alienating artificiality of the modern world and its consequences.This paper will successively focus on three aspects of the Pre-Raphaelite relationship to the modern city. The first aspect is its representation: the city is a fatal beauty which seduces and corrupts, winds its network around the characters, and whose façades hide only death. This criticism opens the way to an attack against urban modernity, characterised by unnatural excess and human alienation. Beings are reified and despised, used and abused, and finally lost in a haze that separates them from any source of meaning – all this the fruit of a capitalist vision of the world. After this criticism comes a proposal: a return to what is the essential part of humanity. The definition of this “human essence” may vary depending on the author, but always centres on intimate knowledge of oneself, God, or others. The modern city is not absolute evil: even its corruption is a thing of beauty. But it is only a half-drawn canvas that the Pre-Raphaelite project tries to achieve, by opening the way for humanity to realize its full potential.